The Influence of Quartet Card Media on Indonesian Language Learning toward Reading Comprehension Skills of Class IV Students - Putri, Maulana; Achmad, Widya Karmila Sari; Pada, Amir (Jurnal Review Pendidikan Dasar : Jurnal Kajian Pendidikan dan Hasil Penelitian, 2025)
This study aims to describe students’ reading comprehension skills before and after the implementation of quartet card media, as well as to determine the influence of this media on improving reading comprehension skills of fourth grade students at UPT SD Inpres 10/73 Turu Cinnae. The research employed a quantitative approach with a one-group pretest–posttest design. The subjects consisted of 12 students selected as the experimental group. Data were collected through reading comprehension tests and observation, and analyzed using descriptive and inferential statistics with SPSS 23. The results showed that the students’ average pretest score was 70.67 (categorized as sufficient), while the average posttest score increased to 88.58 (categorized as very good). The paired sample t-test revealed a significance value of sig. (2-tailed) < 0.05, indicating a significant difference between pretest and posttest results. Therefore, it can be concluded that the use of quartet card media has a positive and significant effect on improving students’ reading comprehension skills.